Konsep Pengembangan Kurikulum Pendidikan Islam Perspektif Prof. Dr. Muhaimin, MA - Amru Almutasim (Prodi PAI Fakultas Tarbiyah IAI Uluwiyah Mojokerto, 2019)
Development of Islamic Education Curriculum in the Muhaimin concept is an activity of producing Islamic religious education curriculum through a process that links one component to another to produce a better Islamic religious education curriculum. In the implementation of curriculum development, it is based on curriculum functions which are at the same time a function of curriculum development in Islamic education. Muhaimin, divided the function of the curriculum into several subjects that play a role in educational activities, including: a) for the school concerned, b) for the schools / madrasas above, c) for the community as users of graduates. According to Muhaimin in the development of Islamic religious education curriculum can use an eclectic approach, which can choose the best of the four approaches below, which are in accordance with its characteristics. These approaches include: a) the subject approach, b) the humanistic approach, c) the technological approach, d) the social reconstruction approach. Whereas in the Islamic education curriculum development model Muhaimin offers a model for developing curriculum based on quality improvement in madrasas and a competency-based curriculum development model in Islamic Higher Education.